2021
DOI: 10.1186/s12903-021-01466-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of parents' knowledge, attitudes, and practices regarding self-medication for their children’s dental problems during the COVID-19 pandemic: a cross-sectional survey

Abstract: Background Self-medication refers to taking medicine without consultation with a doctor or dentist, and it is an important health issue, especially during the COVID-19 pandemic. There are no data about parents’ SM practices for their children’s dental problems during the COVID-19 pandemic. The present study aims to evaluate parents’ knowledge, attitudes, and practices regarding self-medication for their children’s dental problems during the COVID-19 pandemic in Northern Turkey. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In the present study, 69% of the questionnaires were filled out by mothers, which reflects the fact that mothers mainly address the treatment needs of their children. This finding was similar to gender distribution of the parents who participated in a similar study [12]. According to the present results, 70% of the current dental visits were due to the consequences of untreated previous carious lesions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, 69% of the questionnaires were filled out by mothers, which reflects the fact that mothers mainly address the treatment needs of their children. This finding was similar to gender distribution of the parents who participated in a similar study [12]. According to the present results, 70% of the current dental visits were due to the consequences of untreated previous carious lesions.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, only 9% of the parents reported benefitting from remote dental consultations. Sen Tunc et al [12] reported selfmedication by 70% of the parents to alleviate dental pain in their children during the COVID-19 pandemic. In a retrospective study on online pediatric dental consultations in Wuhan, China, 40% of the consultations were about emergency conditions; 98% of which were related to toothache, swelling, or dental trauma [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is inevitable that patient flows are not as high as they used to have economic effects. Among these effects, the decrease in working hours with the transition to flexible working hours can be counted as the dismissal of salaried dentists and other clinical staff (30,31). These situations can lead to unpredictable longterm results such as unemployment.…”
Section: Since Our Study Was Conducted On Patients Who Applied To Karabük Oral and Dental Health Training And Researchmentioning
confidence: 99%
“…Majority of the respondents were able to express themselves satisfactorily and clearly (19). A recent study from Google interest trends on self-medication during the COVID-19 pandemic depicted an increase in the number of searches regarding self-medication, which indicates the need to reach out to the population in different ways, one of which can be through teledentistry, as reported by Sen Tunc et al (20).…”
Section: Recent Evidence Of Teledentistrymentioning
confidence: 74%